Analisis Faktor – Faktor Kepatuhan Wajib Pajak UMKM Di KPP Pratama Padang Dua - Fajri Hidayat; Nini (CV. ITTC INDONESIA, 2023)
This research aims to determine and analyze the influence of tax sanctions, taxpayer awareness, understanding of tax regulations, and modernization of the tax administration system on MSME taxpayer compliance at KPP Pratama Padang Dua, both partially and simultaneously. This research was conducted on MSME taxpayers in East Padang District which are within the scope of KPP Pratama Padang Dua, using a quantitative approach. The sampling method is Non-Probability Sampling with Convenience Sampling techniques with a sample size of 105 people. The data collection technique is a questionnaire technique. The data analysis used is multiple linear regression. The results of this research show that the tax sanctions variable has no effect on MSME taxpayer compliance, the taxpayer awareness variable has an effect on MSME taxpayer compliance, the tax regulation understanding variable has an effect on MSME taxpayer compliance, the administrative system modernization variable has no effect on MSME taxpayer compliance. Simultaneously, tax sanctions, taxpayer awareness, understanding of tax regulations, and modernization of the administrative system influence MSME taxpayer compliance.